2022
DOI: 10.3390/ijerph191912893
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Type II Cell Damage and Nrf2-SOD1 Pathway Downregulation Are Involved in PM2.5-Induced Lung Injury in Rats

Abstract: The general toxicity of fine particulate matter (PM2.5) has been intensively studied, but its pulmonary toxicities are still not fully understood. To investigate the changes of lung tissue after PM2.5 exposure and identify the potential mechanisms of pulmonary toxicity, PM2.5 samples were firstly collected and analyzed. Next, different doses of PM2.5 samples (5 mg/kg, 10 mg/kg, 20 mg/kg) were intratracheally instilled into rats to simulate lung inhalation of polluted air. After instillation for eight weeks, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“… 94 After being exposed to PM2.5, it is observed that there are fewer multilamellar bodies in the Alveolar epithelial type II; cell (AT2) increases mitochondrial swelling, collagen deposition, and pulmonary inflammation. 95 In addition, it can be observed that the dysregulated AT2 cells into AT1 cells in the PM2.5-induced COPD mouse model 96 damage cellular repair mechanisms. Even worse, it has been shown that inflamed bronchial epithelial cells caused by air pollution particles trigger apoptosis, 97 particularly when PM2.5 is injected into those inflamed by cigarettes.…”
Section: Pm25 Induced Pathogenesis In Copdmentioning
confidence: 99%
“… 94 After being exposed to PM2.5, it is observed that there are fewer multilamellar bodies in the Alveolar epithelial type II; cell (AT2) increases mitochondrial swelling, collagen deposition, and pulmonary inflammation. 95 In addition, it can be observed that the dysregulated AT2 cells into AT1 cells in the PM2.5-induced COPD mouse model 96 damage cellular repair mechanisms. Even worse, it has been shown that inflamed bronchial epithelial cells caused by air pollution particles trigger apoptosis, 97 particularly when PM2.5 is injected into those inflamed by cigarettes.…”
Section: Pm25 Induced Pathogenesis In Copdmentioning
confidence: 99%